Needs Analysis in Developing Digital Flashcards for Indonesian Language Learning in Elementary School - Hanisah, Hanisah; Sutomo, Moh; Saihan, Saihan (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to analyze the needs in developing digital flashcards in Indonesian language learning to increase reading interest. The analysis was conducted through a qualitative case study with the research subjects selected by purposive sampling, including the principal, curriculum deputy, grade 1 teacher, and 30 students. Data collection methods involved observation, interviews, documentation, and learner questionnaires, with analysis using triangulation techniques. The results showed a lack of utilization of digital learning media, especially digital flashcards, at MI Daru Falah Wirowongso Jember, especially in grade 1, to support learners' interest in reading. In response to these findings, researchers analyzed the needs that can be implemented in the development of digital media, especially digital flashcards. The implications of this research are expected to provide a more comprehensive view of the needs of Indonesian language learning in the digital era, as well as providing a foundation for further development in increasing students' interest in reading through relevant and effective learning media.